Study of Energy Scattering Relation and RCS Reduction Characteristic of Matrix-Type Coding Metasurface - Jia Ji Yang; Yong Zhi Cheng; Dong Qi; Rong Zhou Gong (Applied Sciences, 2018)
In this paper, we present a design of the linear polarization conversion metasurface (MS) for the broadband radar cross section (RCS) reduction based on split-ring resonator (SRR) structure in microwave region. The corresponding phase gradient can be obtained through the stable phase difference of basic units of polarization conversion MS. The designed polarization conversion MS is applied in coded electromagnetic (EM) matrix by defining two basic units “0” and “1”, respectively. Based on the principle of planar array theory, a new random coding method named by matrix-type coding is proposed. Correlative RCS reduction mechanism is discussed and verified, which can be used to explore the RCS reduction characteristic. The simulated linear polarization conversion rate of the designed structure is up to 90% in the frequency range of 6–15 GHz, and the RCS reduction results verify the theoretical assumptions. Two kinds of matrix-type coding MS samples are prepared and measured. The experimental results indicate that the reflectance of MS is less than –10 dB on average under normal incidence in frequency range of 5.8–15.5 GHz. The average RCS reduction is essentially more than 10 dB in frequency range of 5.5–15 GHz and the corresponding relative bandwidth is 92.7%, which reasonably agrees with simulation. In addition, excellent RCS reduction characteristic of the designed MS can also be achieved over a wide incident angle.